Lipid-based nanoformulation of irinotecan: dual mechanism of action allows for combination chemo/angiogenic therapy. (November 2011) - Waterhouse, Dawn N; Yapp, Donald; Verreault, Maite; Anantha, Malathi; Sutherland, Brent; Bally, Marcel B
A number of studies have outlined the antiangiogenic effects of cytotoxic agents when administered frequently at low doses. These studies suggest that the effect of the cytotoxic agent is on the vasculature within the tumor and it is assumed that there is little or negligible cytotoxicity. Liposomal drug delivery systems have the ability to provide a dual mechanism of activity where tumor accumulation can deliver high local concentrations of the drug at the site of action with concomitant slow release of the drug from carriers in the blood compartment that results in antivascular effects, similar to that achieved when dosing frequently at low levels. Although this dual mechanism of activity may be linked to other lipid nanoparticle formulations of anticancer drugs, this article summarizes the evidence supporting direct (cytotoxic) and indirect (antivascular) actions of a liposomal formulation of irinotecan.